Penelitian Cloud computing pada Industri, Pendidikan, Kesehatan, Transportasi, dan Perbankan - Zahra, Awanda Fitya; Kusuma, Zulfa Hady; Putra, Irkhamnawan Dikmanta; Arifin, Rahmat Fadli; Fadhila, Zahra Nur; Amrozi, Yusuf; Rozzika, Cholifatur (JURNAL TEKNOLOGI INFORMASI, 2023)
AbstrakTeknologi adalah sarana yang mempermudah aktifitas sehari-hari, semakin berkembangnya zaman juga semakin berkembang pula teknologi. Khususnya teknologi cloud computing yang telah banyak membantu dalam berbagai aspek di bidang industri. Dengan ini, penulis mengkaji lebih dalam tentang teknologi cloud computing menggunakan metode deskriptif kualitatif. Teknik pengambilan data menggunakan studi kepustakaan dengan menelusuri dan mengulas sumber-sumber literatur pada jurnal. yang kemudian disusun, dipaparkan, dan dilakukan analisis data menggunakan pendekatan analisis perbandingan. Cloud computing memiliki fungsi yang sangat dibutuhkan oleh berbagai bidang industri, seperti industri pendidikan untuk sarana pembelajaran, industri kesehatan sebagai penyedia layanan dan konsultasi, industi transportasi sebagai penyedia akses transportasi dimana saja, dan industri perbankan untuk menyediakan keamanan kepada para pengguna bank.AbstractTechnology used to facilitates human bieng on their daily routine activity. Technology has been rapidly growing as the time progress. In the case of Cloud computing technology has that been used a lot in various aspects in the industrial sector. With this, the author examine deeply about cloud computing technology using qualitative descriptive method. The technique of collection data used literature study by tracing and reviewing literature sources in journals. With this, the authors review more deeply about cloud computing technology using a qualitative descriptive method. The data collection technique used literature study by tracing and reviewing literature sources in journals. Then compiled, presented, and conducted the data analysis using a comparative analysis approach. Cloud computing has functions that are needed by various industrial fields, such as the education industry for learning facilities, the health industry as a service and consulting provider, the transportation industry as a provider of transportation access anywhere, and the banking industry to provide security to bank users.